Qur'anic solutions to working women's problems in workplace - Hossen, Belayet; Osmani, Noor Mohammad; Elatrash, Radwan Jamal Yousef (2018)
This paper describes some major problems of working women in Bangladesh, especially in garment industry which is regarded to be the second highest foreign currency earner among other sources of Bangladesh economy. In Bangladesh, there are more than six thousand garment industries where around six million people work and majority of them are women. The problems faced by these working women are extreme in nature. It may pose a serious threat to the development of Bangladesh economy. The research asserts that if these problems persist and not tackled effectively, the number of working women will gradually diminish; consequently, the economic growth of Bangladesh will stand far from its desired goal.